2021
DOI: 10.3389/fmicb.2021.593202
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Highly Pathogenic H5N6 Avian Influenza Viral Pathogenicity and Inflammatory Response in Chickens and Ducks

Abstract: Infection with H5N6 highly pathogenic avian influenza virus caused high mortality in chickens, while ducks often appear to be asymptomatic. But, some recent H5Nx subtype viruses could cause high mortality in ducks. The variation between different species and the mechanisms by which some H5Nx viruses cause death in ducks requires investigation to identify the key processes in influenza susceptibility and pathogenesis. Here, we characterized two representative H5N6 viruses, A/Pavo cristatus/Jiangxi/JA1/2016 (JA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
(90 reference statements)
3
4
0
Order By: Relevance
“…Similar results have been reported in Mandarin ducks with clade 2.3.4.4e H5N6 HPAIVs [24,33]. In another study, most mallards died of infection within 8 weeks after being infected with clade 2.3.4.4e A/Pavo cristatus/Jiangxi/JA1/2016 (H5N6) [25], while those infected with another clade 2.3.4.4 strain, A/Anas crecca/shanghai/SH1/2016 (H5N6), caused no signs of infection. These results suggest that pathogenicity of clade 2.3.4.4e HPAIVs in Anatidae varies depending on the strain.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar results have been reported in Mandarin ducks with clade 2.3.4.4e H5N6 HPAIVs [24,33]. In another study, most mallards died of infection within 8 weeks after being infected with clade 2.3.4.4e A/Pavo cristatus/Jiangxi/JA1/2016 (H5N6) [25], while those infected with another clade 2.3.4.4 strain, A/Anas crecca/shanghai/SH1/2016 (H5N6), caused no signs of infection. These results suggest that pathogenicity of clade 2.3.4.4e HPAIVs in Anatidae varies depending on the strain.…”
Section: Discussionsupporting
confidence: 85%
“…Little is known about the pathogenicity of clade 2.3.4.4e HPAIVs in Anatidae. Mandarin ducks inoculated with the clade 2.3.4.4e HPAIVs showed inapparent infection with virus shedding via the oral route [24]; Wang et al [25] reported that some 2.3.4.4e HPAIVs demonstrated relatively higher pathogenicity in mallards, accompanied by the excessive expression of iNOS in the brain.…”
mentioning
confidence: 99%
“…In this study, the amino acid sequences at the cleavage sites of the HA genes of 3 isolates were all continuous basic amino acids, which was in line with the characteristics of highly pathogenic avian influenza virus (HPAIV) [13]. Previous studies have shown that amino acid mutations such as S133A, I151T, T156S, Q222L, S/R223N, G224S, P235S and E251K can change the affinity of AIV for human and avian receptors, especially the mutations of Q222L and G224S were the most critical [14]. In our study, amino acids Q222 and G224 of the HA proteins of the 3 viruses were not mutated (Table 1), so they retained the ability to bind to the avian receptor α2-3 galactosylsialic acid (SAα2-3Gal).…”
Section: Characteristics Of 3 Strains Of H5n6 Subtype Aivsupporting
confidence: 63%
“…Similar results have been reported in Mandarin ducks with clade 2.3.4.4e H5N6 HPAIVs [ 24 , 33 ]. In another study, most mallards died of infection within 8 weeks after being infected with clade 2.3.4.4e A/ Pavo cristatus /Jiangxi/JA1/2016 (H5N6) [ 25 ], while those infected with another clade 2.3.4.4 strain, A/ Anas crecca /shanghai/SH1/2016 (H5N6), caused no signs of infection. These results suggest that pathogenicity of clade 2.3.4.4e HPAIVs in Anatidae varies depending on the strain.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the pathogenicity of clade 2.3.4.4e HPAIVs in Anatidae. Mandarin ducks inoculated with the clade 2.3.4.4e HPAIVs showed inapparent infection with virus shedding via the oral route [ 24 ]; Wang et al [ 25 ] reported that some 2.3.4.4e HPAIVs demonstrated relatively higher pathogenicity in mallards, accompanied by the excessive expression of iNOS in the brain.…”
Section: Introductionmentioning
confidence: 99%